2022
DOI: 10.30939/ijastech..999261
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Effects of Fuel Injection Timings on Dimethyl Ether (DME) Energy Share Improvement and Emission Reduction in a Dual-Fuel CRDI Compression Ignition Engine

Abstract: The impacts of different fuel injection timings (base (15BTDC) and retarded (12BTDC)) on a single cylinder common rail direct injection (CRDI) compression ignition (CI) engine under dual fuel mode (DME-diesel) was examined at the maximum torque with the engine speed of 2200 rpm. The diesel (liquid) fuel was directly injected into the engine’s cylinder at the end of the compression stroke and Dimethyl ether (gas) fuel was injected into the intake system of the engine during the suction stroke. The maximum DME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…They have also implied that imep decreased with the increase of DEE addition in the fuel mixtures. Rate of pressure rise rate decreased from 5.08 bar/ °CA to 3.1 bar/ °CA with diesel and optimum 52% DME ES (energy share) respectively in a dual fuel CRDI CI engine [31]. In the work of Ardebili et al, [30], engine torque decreased with DEE addition from 40% to 70% ratio.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…They have also implied that imep decreased with the increase of DEE addition in the fuel mixtures. Rate of pressure rise rate decreased from 5.08 bar/ °CA to 3.1 bar/ °CA with diesel and optimum 52% DME ES (energy share) respectively in a dual fuel CRDI CI engine [31]. In the work of Ardebili et al, [30], engine torque decreased with DEE addition from 40% to 70% ratio.…”
Section: Resultsmentioning
confidence: 92%
“…Optimum response variables were determined as 11.80 Nm engine torque, 268 g/kWh BSFC, 1.365 COVimep [30]. Shere and Subramanian [31] investigated the effects of fuel injection timings with diesel/DME. Diesel injected into the cylinder where as DME was injected into the inlet line.…”
Section: Introductionmentioning
confidence: 99%
“…where ma denotes air mass flow rate (kg/s). 𝜌a, vs, and N respectively symbolize density of air (kg/s), swept volume (m 3 ), and engine speed (min -1 ) [30].…”
Section: 𝑑𝛳 𝛳𝑑𝛳 𝐸𝑉𝑂 𝐼𝑉𝐶mentioning
confidence: 99%
“…The International Energy Agency (IEA) states that developing countries' energy consumption will increase by 25% by 2040, which will trigger the formation of more greenhouse gases and the negative effects of climate change [5,9]. Global programs such as the Sustainable Development Goals (SDGs) also emphasize the urgency of transitioning to sustainable energy sources [10,11]. In addition to its negative effects, the depletion of fossil fuel resources has increased the search for alternative methods to use these resources more efficiently and reduce their negative effects [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies such as the use of biodiesel fuels, engine modifications, and the addition of fuel additives are examples of studies carried out to reduce the negative effects mentioned above and to use resources more efficiently [20][21][22]. In case studies using biodiesel fuel and nanoparticles, it has been shown that engine performance can be significantly increased, and harmful emissions can be reduced [23][24][25].…”
Section: Introductionmentioning
confidence: 99%